Perubahan Pola Perilaku Mahasiswa Fisip Pasca Pandemi Covid-19 Di Universitas Pramita Indonesia Kabupaten Tangerang - Asri Setiani; Intan Rachmina Koho; H.M. Arifin Daulay (Lensa, 2022)
The Covid-19 pandemic has changed many components of learning methods. Anxiety and lack of self-confidence experienced by students by using as much as possible must be addressed rationally so that graduates can continue their studies. First, what is the direction of changing lifestyles among students after the end of the Covid-19 pandemic. Second, what are the possible changes and changes in behavior patterns. This observation is intended to see and provide explanations for adjustments in the behavior of FISIP students during the COVID-19 pandemic at Pramita Indonesia University. This observation uses a literature study approach, observing various data from the latest news reports, as well as studying objects that are directly related to them with scientific data and literature from various sources. This study uses the behavioristic principles of Burrhus Frederic Skinner and various applicable theories regarding behavioral relationships. The effect of this study shows that skilled behavior adjustment with the help of FISIP students at Pramita Indonesia University needs to adapt, FISIP students who accept, understand, get used to new habits, are able to reduce the effects of tradition shock.